2013
DOI: 10.1111/jsm.12054
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Solutions for the Complications of the Vaseline Self-Injection of the Penis

Abstract: Introduction Penile girth enhancement by the injection of Vaseline is an existing practice. Many cases develop severe complications that need surgery. Aim To report on the reconstructive surgical solutions of the complications of Vaseline self-injection and the outcomes. To develop a modification of a one-step reconstruction method involving the use of pedicled scrotal flaps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
0
17
0
3
Order By: Relevance
“…Penile reconstructive surger y is in continuous development, but remains an anatomic, functional and aesthetic challenge especially in cases with severe complications after illicit, self-injection [9]. The most used self-injected chemical substances are mineral oils, vaseline, paraffin oils and kanamycin [5,6]. In these abovementioned cases, reconstruction with scrotal flap technique seems a good choice, if it's not possible, skin grafts may be used from other parts of the body [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Penile reconstructive surger y is in continuous development, but remains an anatomic, functional and aesthetic challenge especially in cases with severe complications after illicit, self-injection [9]. The most used self-injected chemical substances are mineral oils, vaseline, paraffin oils and kanamycin [5,6]. In these abovementioned cases, reconstruction with scrotal flap technique seems a good choice, if it's not possible, skin grafts may be used from other parts of the body [9].…”
Section: Resultsmentioning
confidence: 99%
“…Consequences following injection are devastating, affecting the sexual and cosmetic function of the penis [2]. Complications can vary depending on the amount of substance that has been administered, personal tolerance, and hygiene conditions [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific complications included phimosis, Vaseline granulomas, ulceration and necrosis, and that following surgical intervention 91% reported satisfactory sexual function. 8 Aside from genital disfiguration that occurs following Vaseline self-injection, skin necrosis, embolisation, blindness and death have also been reported. 9 Moon et al have studied the psychological impact of penile paraffinoma and reported (a) the majority of procedures were performed by non-medical personnel, (b) a higher incidence among incarcerated persons, and (c) peer recommendation prior to imprisonment was commonplace.…”
mentioning
confidence: 99%
“…The main motivation for the intervention is the fellow prisoners' bad example, so the information of these subpopulations about the harmfulness and ineffective nature of vaseline self-injection is of essential importance. Our study of demonstrating the high incidence of complications of the petroleum jelly injection emphasizes the importance of prevention and education programs in order to improve the health and social status of the affected sub-population (Rosecker et al, 2011(Rosecker et al, , 2012Bajory et al, 2010Bajory et al, , 2013). …”
mentioning
confidence: 99%